Comparing The Effectiveness Of Meta- Emotion Based Couple Therapy with Narrative Couple Therapy On Adjustment And Cuople Burnout In Conflicting Couples - sakineh fotohi; niloufar mikaeili; akbar atadokht; nader hajlo (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2018)
Aims:The present study was conducted with the aim comparison of the effectiveness of meta-emotion based couple therapy with narrative couple therapy on adjustment and cuople Burnout in conflicting couples. Materials & Methods: This research is a type of experimental study with pre test - post test design and control group. The statistical population of the study included all incompatible couples referring to the family court, dispute resolution councils andTabriz counseling centers during the autumn of 2015.To select the statistical sample among couples are eligible to enter the study were selected 24 couples (48 people) and were randomly assigned into two experimental groups and one control group and then Was implemented meta- emotion based couple therapy and narrative couple therapy during 8 sessions of 90-minute for the expremental groups.To collect research data, it was used of Pinez burnout scale and dyadic adjustment scale In both preand post-test.Data analysis was performed using multivariate analysis of covariance in SPSS. findings: data analysis showed that the group receiving meta-emotion based couple therapy compared to the group of narrative couple therapy and control group; and also the group receiving narrative couple therapy versus control group average scores had increased in the marital adjustment and decreased in the cuople burnout.Conclusion:According to the results meta- emotion based couple therapy regarding to their compilation nature and the use of the principles and principles of the various therapeutic theories comparing the narrative couple therapy it has more efficacy on increasing marital adjustment and reducing cuople burnout of conflicting couples.